Visual semiotic mode of perfume advertisements - Nikiforova , Yevhenia; Popivniak , Olena; Galitska, Elizaveta (Current issues of Ukrainian linguistics: theory and practice, 2023)
The article deals with peculiarities of perfume advertisements, in particular, their visual semiotic mode structure and its constituents creating the recognitive features of this mode. Constituents-details are recognized as visual formal elements which bear main and significative visual information. The central objects of this research are perfume advertisements and their visual formal elements which create the whole visual semiotic structure. All formal elements are divided into three functional groups according to their function in the visual space of advertisements. Primary group of visual formal elements performs the delimitative function. This function represents the contouring of formal elements as separate objects (product, model, and background). Secondary group of visual formal elements provides the embodiment. This function represents the outline, when formal elements of the primary group are filled with structural components – formal elements (line, plane, composition, depth (space), shape). Intermediate group of visual formal elements performs the colourative function when formal elements of primary and secondary groups are coloured. This group is formed with variations of colours. Within the visual semiotic mode each group (primary, secondary, and intermediate) includes formal elements which demonstrate complex and integrative nature of visual inner structural organisation. Visual formal element of any group has its own boundary, shape, or outline, border and function. Another feature of formal elements is a set of parameters. They are recognized as qualitative and quantitative characteristics of formal elements. Parameters are bearers of attributes. The main function of parameters is to accompany any formal element making it distinctive, recognizable, well-developed. Division of formal elements into some related and corresponding smaller sub-elements reflects the integrated and complex nature of visual semiotic mode and its formal elements. Formal elements are separated into sub-elements. Simultaneously parameters are dissociated into sub-parameters. Correlation of formal element-parameter reflects the boundaries between these units as clear-cut. Boundaries in the system of sub-units (sub-element – sub-parameter) are diffusive. Integrated nature of visual semiotic mode is connected with the existence of intermediate sub-state which is formed with corresponding sub-units. These sub-units function together in the state of self-equilibrium which gives the visual semiotic mode some flexibility. It happens when boundary between sub-units becomes diffusive and transparent. Sub-elements and sub-parameters percolate mutually through that weakened boundary. That mutual percolating leads to the mutual mixing when recognitive features of sub-elements and sub-parameters become common and shared for sub-units. Flexibility is supported with the dense net of sub-parameters and colouration of all visual formal elements.